Severity assessment of acute pancreatitis: applying Marshall scoring system - Carioca,André Lanza (2015)
Objective: To analyze the effectiveness of the Marshall scoring system to evaluate the severity of acute pancreatitis (AP). Methods : We performed a prospective, observational study in 39 patients with AP evaluated by the Marshall scoring system and the Ranson criteria (admission and 48 hours). We assessed the progression of the disease for seven days and compared the data of the two criteria. Results : Seven patients died during the observation period and one died afterwards. All deaths had shown failure of at least one system by the Marshall method. Conclusion : The Marshall scoring system may be used as an effective and simplified application method to assess the severity of acute pancreatitis.